Comparison of dynamic viscoelastic and physicochemical properties of pressurised and pasteurised longan juices with xanthan addition - Chaikham P. (2014)
Physical and biochemical properties of pressurised and pasteurised longan juices with various xanthan additions, such as viscoelastic behaviour, colour L (lightness), -a (greenness), b (yellowness), ΔE (total different colours) and BI (Browning Index) parameters, polyphenol oxidase (PPO) activity, ascorbic acid, gallic acid, ellagic acid, total phenols and antioxidant capacity (DPPH assay) were studied. Viscoelastic determination indicated that longan juice with 0.15% xanthan addition was optimal for a fruit drink. Colour parameters showed pressurised longan juice at 500 MPa was brighter and more transparent than fresh and other processed juices. PPO was completely inactivated in pasteurised juices, whereas in pressurised juices at 300 and 500 MPa, the activities were more than 100% and 95-99%, respectively. Bioactive components including ascorbic acid were significantly reduced according to treatment severities, whereas gallic and ellagic acids were relatively stable in all processed juices. Total phenols and DPPH radical-scavenging activity decreased significantly on pasteurisation, but were stable on pressurisation. © 2012 Elsevier Ltd. All rights reserved.